A patient with a diagnosed patent ductus arteriosus – what next? - Kukawczyńska-Noczyńska, Joanna; Bortnowska, Katarzyna; Kukawczyńska, Elżbieta (Pediatria Polska - Polish Journal of Paediatrics, 2018)
Among congenital heart defects of the cardiovascular system, patent ductus arteriosus (PDA) comprises about 10% in the general population. Prematurity significantly raises the likelihood of PDA: in preemies of very low birth weight this defect appears with a frequency up to 65%, and in extremely low birth weight preemies up to 80%. Over a span of many years of research many different methods for treating PDA have been discovered, modified, and improved. Invasive treatment (thoracotomy, thoracoscopy, and percutaneous closure) as well as therapeutic strategies (symptomatic treatment, pharmacological treatment) allow for complete closure of PDA in every patient. The limitations of particular methods in regard to age and body mass of the child, their clinical state, as well as the morphology of the PDA itself, require careful analysis when choosing the appropriate treatment method based on the effectiveness and permanency of closing the duct as well as minimal invasiveness. Among preemies and newborns it is possible to close the PDA using symptomatic and pharmacological treatment as well as through thoracotomy and thoracoscopy, while in older children and adults the method of choice is the percutaneous closure of PDA. Matching the correct treatment strategy with the clinical situation is key to the successful closure of the duct. Presented in the text below is an overview of available methods and their usefulness in treating PDA.